(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The transition from the SPOD world to the VUCA world has significantly changed the operating environment of organizations. The main features of the comfortable and familiar SPOD world for most organizations were stability, predictability, simplicity, and certainty. The VUCA world has significantly complicated and changed the functioning of organizations, as its distinctive features are instability, uncertainty, complexity, and ambiguity. In the new conditions, the risks of business loss (stoppage), cyberattacks and cybercrime, environmental damage and climate risks, and political risks became the biggest risk for the successful functioning of business. The VUCA world has presented new challenges to modern managers: geopolitical changes and globalization; development of new business models; technological changes; sustainability and social responsibility; change management. Special needs arose to ensure the flexibility and adaptability of organizations, the ability to develop and implement changes. The paradigm of management and requirements for the competence of managers of modern organizations have also changed. It is substantiated that the ability of managers to think strategically and develop strategic plans, work in a global space, manage risks, constantly learn and train others, manage personnel based on modern approaches, develop and implement innovations, has become particularly relevant in the VUCA world. The ability to work in a coordinated team, the ability to effectively and quickly carry out digital transformations in the organization gained special importance. Managers of organizations in the VUCA world need to be able to use new technologies and innovations, look for new business opportunities, and develop new markets. It was revealed that the VUCA world is being replaced by the BANI world, the main features of which are fragility, restlessness, non-linearity, incomprehensibility. The era of the development of artificial intelligence and robots is coming. The BANI world creates new opportunities for the development of organizations, brings new risks and sets new requirements. This puts new demands on management and managers and requires further improvement of the management paradigm and managers’ competencies.